Growing on Steroids: Rapidly Scaling the User Base of Digital Ventures Through Digital Innovaton1 - Huang, Jimmy; Henfridsson, Ola; Liu, Martin J.; Newell, Sue (MIS Quarterly, 2017)
Digital ventures, start-ups growing by drawing on and adding to digital infrastructures, can scale their business at an unprecedented pace. We view such rapid scaling as a generative process by which a venture’s user base increases significantly between two points in time through digital innovation. We studied WeCash, a Chinese digital venture, nearly doubling its user base monthly, to learn more about this generative process. We trace three contingent mechanisms underpinning rapid scaling: data-driven operation, instant release, and swift transformation. We explain these mechanisms and how they interact in the rapid scaling of digital ventures. The research offers an agency perspective on scaling of digital ventures that speaks to the digital innovation literature.